FAKTOR-FAKTOR LANGSUNG YANG MEMPENGARUHI USIA MENOPAUSE - Esa Risi Suazini (LPPM Universitas Muhammadiyah Tasikmalaya, 2019)
One indicator of the Human Development Index (HDI) is Life Expectancy (AHH). Garut has AHH 70.84 years, this figure is lower than other regions. Long life reflects health status. A woman if she is long-lived will definitely experience menopause. Healthy menopause is an indicator of happiness. The menopause will be accompanied by problems. How to repeat the problem by realizing happiness, and slowing down the age of menopause. This study aims to determine what factors influence menopause. The factors that will be examined are the factors that play a direct role in the reproductive organs, namely the age of menarche, parity and contraception. This study is an analytical study with a crossectional approach, spearman test and linear regression test. Respondents in this study were 95 people. Determination of samples with purposive sampling in menopausal women in Garut. Independent variable age of menarche, parity and contraceptive use, dependent variable age of menopause. The results of the bivariable analysis, the p value of menarche age 0.163 (no correlation), parity 0.140 (no correlation) and contraceptive use 0.044 (had a significant correlation). The results of the linear regression test obtained data on the effect of non hormone contraception or not using contraception to slow menopause by 0.02%. Conclusion, only the contraceptive use factor has an influence on the age of menopause.